Trends and impacts of the fourth industrial revolution to digital information environment - Tien, Le Duy (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2019)
During recent years, according to the World Economic Forum, intensive progresses of information technologies (called also as digital technologies) have become driving forces for development of the Fourth Industrial Revolution (4.0 Revolution). Digital technologies of 4.0 Revolution such as S.M.A.C. (Social-Mobility-AnalyticsCloud), IoT (Internet of Things), AI (Artificial Intelligence), AR (Augmented Reality), VR (Virtual Reality) and etc. are changing totally the human communication-information environment: from one side, it links intensively people over the world, and, from another side, it puts many challenges in secured supply of true, objective and social progress supportive information. This paper provides a summary of trends, impacts and challenges from digital technologies in 4.0 Revolution toward the digital environment of the world and press sector. Code: 18100501